PENGARUH KUALITAS PELAYANAN DALAM UPAYA MENINGKATKAN KEPUASAN NASABAH (STUDI PT. BANK MANDIRI TBK BANJARMASIN) - Rory Handriano; - Masrifani (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2021)
Abstract, This research aims to determine the effect of tangibles, reliability, responsiveness, assurance, and empathy on customer satisfaction at PT. Bank Mandiri (Persero) Tbk Cash Office Soetoyo S. Banjarmasin. The method used in this research is descriptive quantitative method, where the instrument or measuring instrument in this study is a questionnaire or questionnaire that contains questions to be responded to by the research respondents using a Likert scale. The results of the research found that there was a positive influence on various aspects of customer satisfaction, but there was a decrease in the number of customers managed in the last few years, which can be seen from the data on the number of customers which relatively decreased from 2017 to 2019 due to low service quality. One of the efforts that can be made by the bank so that the number of customers and service quality can be optimally improved is by providing convenience to customers when making transactions, so that it reflects good quality in accordance with customer expectations in general.